How aware are we regarding vector borne diseases? A community based study in a slum of Kolkata, India - Sahoo, Sanjaya Kumar; Taraphdar, Pranita; Mallick, Ashok Kumar; Dasgupta, Aparajita; Preeti, P. S.; Biswas, Dhiraj (International Journal of Research in Medical Sciences, 2017)
Background: Vector borne diseases (VBDs) form a major part of the communicable diseases in India. Ignorance and impoverished conditions of people contribute in creating source and spread of vector borne diseases and hinder disease control strategy. Slums are more vulnerable to vector borne diseases because of poor environmental condition, standard of living, poverty and ignorance of the people. This study is a small endeavour to highlight the awareness of residents of slum area of Chetla, Kolkata, West Bengal, India regarding vector borne diseases. Objectives were to assess the awareness of the study population regarding different vector borne diseases and to find out the association of awareness with relevant demographic variables. Methods: A community based observational, cross-sectional study was conducted among adult population in a slum area of Chetla, Kolkata, West Bengal, India. Multivariate logistic analysis was done to find out association of awareness with relevant variables. Results: Awareness regarding malaria was good and that of dengue was satisfactory while awareness regarding other vector borne diseases was poor. Age, sex, caste, education and social class were found significantly associated with satisfactory awareness. Younger population i.e. age ≤35years, males, general caste people, literacy status above primary school and social class III and above had better awareness regarding vector borne diseases. Conclusions: This study uncovered the lacunae regarding awareness of the study population regarding vector borne diseases. It can be concluded that intensified efforts towards creating public awareness and mobilizing the community regarding the identified issues should be addressed.